Edukasi Minimalisir Penggunaan Wadah Plastik Melalui Kampanye “Sayangi Bumi Dan Dirimu, Dengan Membawa Bekalmu” - Tosepu, Ramadhan; Effendy, Devi Savitri; Jamustiara, Syakinah; Rahmadhani, Sri; Jono, Tamara Moratono; Ramadhan, Dela; Revalina, Revalina (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
Campaign The purpose of the "Love the Earth and Yourself, by Bringing Your Own Lunchbox" campaign is to educate students about the dangers of using plastic as food containers and to encourage the use of non-plastic food containers among students. An initial survey was conducted to obtain information on the pattern of single-use plastic use among students with a questionnaire developed using the Health Belief Model (HBM) theory approach. The campaign developed educational posters and appointed anti-single-use plastic ambassadors. Through this initiative, it is hoped that Halu Oleo University can become a pioneer in the movement to reduce plastic usage and create a more sustainable campus environment